Using Ontology for Providing Content Recommendation Based on Learning Styles inside E-Learning - Kusumawardani, Sri Suning; Prakoso, Robertus Sonny; Santosa, Paulus Insap (2014)
E-Learning as one of the learning support facilities provides various content types and interaction models inside. This wide range of content types inside e-Learning can be used for accommodating differences in learning styles among the students. In this research, we develop concept mapping between student characteristics and categories by Felder-Silverman Learning Style Model and appropriate content inside a Moodle-based e-Learning. This mapping is represented in the ontology and then implemented in Moodle-based e-Learning system for giving content recommendation to students based on their learning styles. There are some concepts that become basic definition of learning styles and e-Learning contents, and also some rules that is used for inferring content recommendation from the basic definition